A bibliometric analysis on packaging research: towards sustainable and healthy packages. Issue 2 (17th September 2020) - Vila-Lopez, Natalia; Küster-Boluda, Inés
Abstract : Purpose: The basis of this paper is to carry on a bibliometric analysis to investigate how "marketing" decisions have affected "packaging" success in different disciplines. This analysis covers from the first paper published on this topic (in 1956) to the last papers published in 2019. Design/methodology/approach: A total of 1, 170 scientific papers (including 14, 177 citations within those papers) were retrieved from the Web of Science (WOS) and Scopus, dated from 1956 to 2019. Scimat software was used to analyse the data. Findings: The results of this paper show that two main sectors constitute the focus of packaging studies from a marketing approach: food and tobacco. Recently, the main topics of research have evolved towards sustainable and health packaging, concerning different agents involved in packaging decisions: retailers, marketers, consumers and producers. So, both lines of research represent promising lines of research. Originality/value: Three different investigating profiles (i.e. engineers, marketers-psychologists and doctors-scientists) have examined how packaging should be prepared to succeed. However, a holistic bibliometric analysis about "packaging" and "marketing" is missing from those three branches of knowledge. This study is important to guide future lines of research to fill the identified gaps.